The second order multi-valued boundary value problem and impulsive neutral functional differential inclusions in Banach spaces - Wei, L.; Zhu, Jiang (Нелінійні коливання, 2008)
In this paper, by using the new fixed point theorem of O’Regan and Precup and noncompact measure,
the existence of solutions of second order multivalued boundary-value problem in Banach spaces and
the existence of a mild solution for impulsive neutral functional differential inclusions in Banach spaces
are studied. The compactuess conditions and the upper semicontinuity conditions of multivalued integral
operators are weaken in this paper. З використанням нової теореми О’Регана та Прекупа, а також некомпактної мiри доведено iснування розв’язкiв багатозначної граничної задачi другого порядку в банахових просторах. Вивчається iснування помiрного розв’язку диференцiальних включень з iмпульсною дiєю
та нейтральним функцiоналом у банахових просторах. У роботi послаблено умови компактностi та верхньої напiвнеперервностi на багатозначнi iнтегральнi оператори.